ORGANIZATIONAL MANAGEMENT STRATEGY IN THE CONTEXT OF DIGITALTRANSFORMATION - TRUNINA, Iryna; SAKUN, Lesia; SHYSHLOVA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is dedicated to analyzing the integration of project management into the organizational management strategy, particularly in the context of digital transformation, highlighting its importance for ensuring the effectiveness and adaptability of organizations. In the face of rapid technological changes, the integration of project management becomes a critical element for achieving strategic objectives and maintaining competitiveness. The study reveals that key elements of this integration include aligning project priorities with the long-term strategic goals of the organization, optimal resource allocation, and effective monitoring and evaluation of goal achievement. The use of tools based on Artificial Intelligence (AI) and Big Data analytics is emphasized, which allows for process automation, reduces decision-making time, improves analytical accuracy, and enhances project management efficiency. The article also discusses the importance of combining agile management methodologies with innovative technologies, which not only optimizes project processes but also ensures transparency of information flows, essential for effective project management at all stages. The research shows that integrating project management into the organizational management strategy allows organizations to achieve high competitiveness and stable growth while effectively adapting to market changes. To improve organizational adaptability in a rapidly changing business environment, a combined management model is proposed, integrating agile methodologies, cutting-edge technologies, and decision support systems. This model can be applied by future teams to effectively achieve strategic goals in the context of digital transformation, helping organizations optimize their processes and become more competitive in global markets.